Evaluasi SIMDA Keuangan dan SIMBAPER Pada Dinas Pendidikan dan Kebudayaan Kabupaten Sragen Tahun 2018-2020 - Rizka Nur Rahmawati (Polytechnic of State Finance STAN, 2022)
The government accounting information system is a tool for producing quality financial reports. The Regional Government of Sragen Regency has implemented an accounting information system with the SIMDA and SIMBAPER applications to manage inventory used for operational activities. This study aims to find out how the implementation and quality of the inventory accounting information system that has been used in the SKPD. The discussion was carried out using descriptive qualitative methods with data from field research in the form of SIMDA Financial and SIMBAPER application practices, library research, and documentation. From the results of observations and interviews, no integration was found between SIMDA Finance and SIMBAPER. Therefore, the inventory accounting information system used by the SKPD needs evaluation and updating in order to produce higher-quality accounting information and financial reports. Keywords: Government accounting information system, SIMDA, SIMBAPER, Inventories